Зоонимната фразеологиjа и надворешниот изглед на човекот (на материjал од македонскиот jазик) - МИРЧЕВСКА-БОШЕВА, БИЉАНА (SlavVaria, 2021)
Zoonymic phraseology and external Appearance (On Macedonian language material). Zoonyms as an important and numerous lexical layer are often in the focus of interest of linguists. In this paper, zonyms are considered as an integral component of the phrasemes in which they experience complete transformation and lose their basic meanings. More specifically, on this occasion we focus on the zonyms in Macedonian language phrasemes that describe the external appearance of man. For this purpose 54 phrasemes were collected and analyzed in order to determine the zonymic components present in the specific units and their impact on the motivation for the formation of the phraseme and in the formation of its meaning.